PERLINDUNGAN KONSUMEN TERKAIT PEREDARAN SAMPO PALSU DITINJAU DARI UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Selian, Della Luysky (Faculty of Law, University of Mataram, 2023)
This research aims to examine and analyze consumer protection related to the circulation of fake shampoo in terms of Law Number 8 of 1999 concerning Consumer Protection. The method used is a normative juridical research method with a descriptive analysis research type. Conclusions from the research results: (1) Consumer protection regarding the distribution of fake shampoo can be seen from the provisions of Article 45 paragraph (1) of Law Number 8 of 1999 concerning Consumer Protection and Article 1365 of the Civil Code. (2) The responsibility of business actors regarding the distribution of fake shampoo is that business actors can provide compensation to consumers related to the distribution of fake shampoo as regulated in Article 19 paragraph (2) of Law Number 8 of 1999 concerning Consumer Protection.